2020
DOI: 10.7704/kjhugr.2019.0038
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and Metabolic Diseases

Abstract: <i>Helicobacter pylori</i> (<i>H. pylori</i>) is one of the most common pathogens that can cause certain gastrointestinal disorders, such as gastritis, peptic ulcers, and gastric cancer. Recently, interest in the systemic effects of <i>H. pylori</i> on extragastric manifestations is increasing. Representative diseases include hematologic, cardiovascular, neurodegenerative, autoimmune, dermatologic, allergic, hepatobiliary, and metabolic diseases. Among them, since the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Clinical manifestations of H. pylori infection include gastrointestinal diseases such as gastritis, peptic ulcer disease, gastric mucosa‐associated lymphoid tissue, and non‐cardia gastric adenocarcinoma 3 . Furthermore, H. pylori infection is linked to a number of extra‐gastric diseases, including idiopathic thrombocytopenic purpura, preeclampsia, cardiovascular disease, neurological, anemia, and autoimmune thyroid diseases 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…Clinical manifestations of H. pylori infection include gastrointestinal diseases such as gastritis, peptic ulcer disease, gastric mucosa‐associated lymphoid tissue, and non‐cardia gastric adenocarcinoma 3 . Furthermore, H. pylori infection is linked to a number of extra‐gastric diseases, including idiopathic thrombocytopenic purpura, preeclampsia, cardiovascular disease, neurological, anemia, and autoimmune thyroid diseases 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…H. pylori infection not only affects the stomach but is also associated with numerous extragastric diseases, including idiopathic thrombocytopenic purpura and iron‐deficiency anemia 8‐10 . Moreover, many studies have reported an association between H. pylori seropositivity and lipid abnormalities, and cardiovascular disease, suggesting a causal relationship that remains controversial 11‐17 …”
Section: Introductionmentioning
confidence: 99%